N-isopropyl-(4-methoxy-3-difluoromethyl)cinnamoyl amide targets mycobacterial MmpL3 - Martinez, Mario David (2024)
Mycobacterial infections still need new and more efficient drugs. In the present work we developed a new and simpler protocol for the synthesis of N-isopropyl-(4-methoxy-3-difluoromethyl)cinnamoyl amide, here named as 3M99F1, a promising candidate for mycobacterial growth inhibition. Using whole genome sequencing of 3M99F1 resistant strains we were able to identify Mycobacterial membrane protein Large 3 (MmpL3) as the target for this compound. MmpL3 inhibition by 3M99F1 was further confirmed by lipid analysis of Mycobacteria in the presence and absence of the drug. MmpL3 is well conserved in Mycobacteria, including atypical or NTM (non-tuberculous mycobacteria) and other Actinobacteria, but it is not present in humans, encouraging the development of new inhibitors using 3M99F1 as scaffold.